“모두 함께 만들고 즐기는 자막”: 플랫폼 기업 주도의 팬 번역에 관한 비판적 분석 - 강지혜; 유한내 (번역학연구, 2021)
This paper analyzes the ways in which fansubbing is represented, carried out and used by Naver V Fansubs, one of the biggest K-pop fansubbing platforms in Korea. The study focuses on the mismatch between the narratives of fansubbing constructed by Naver and the ways in which fan translation and translated texts are actually utilized by the company. It argues that although Naver produces a narrative of fansubbing of videos as an open, self-initiated, and community-building activity, fan translation in the context of Naver V LIVE is in fact an institutional practice that requires fans to follow institutional guidelines and norms, as well as an activity that is hierarchically structured and monitored by institutional actors. More importantly, fansubbing helps to increase traffic to Naver and strengthens its online presence. The data collected from fansubbing activities are channeled to create revenue for this for-profit company, which raises ethical concerns about unpaid digital labor. The study shows that fansubbers are susceptible to financial exploitation of free labor in digital platform economy. The findings suggest that more empirical studies of the fansubbing activities need to be carried out in order to enhance our understanding of the complex interplay between translation and fandom and the ethical implications of platform owners’ utilization of free labor of fans and sourcing of new revenue streams.
Keywords: 플랫폼 경제; 팬 번역; 팬 노동; 온라인 플랫폼; 네이버 브이라이브; platform economy; fansubbing; fan labor; online platforms; Naver V LIVE